Evaluation of Nutrition Support Pharmacist Interventions. (10th October 2014) - Giancarelli, Amanda; Davanos, Evangelia
Abstract : Background: The purpose of this study was to determine the number and types of interventions performed by our nutrition support service (NSS) pharmacists that were not directly related to the nutrition formula prescription. Methods : This was an institutional review board–approved retrospective study of all adult pharmacy NSS consultations from January 1, 2011 to December 31, 2011. All interventions assessed were categorized as the following: fluids and electrolytes, glucose management, alternate therapy, diagnostics, general laboratory result monitoring, vitamin and trace element monitoring, discontinuing medication, adding medication, dose adjustment, and other. The primary endpoint was to determine the total number of interventions and their acceptance rates. The secondary endpoint was to determine which categories had the most accepted and most denied interventions. Results : There were 132 adult consults evaluated with a total of 383 interventions performed. The overall acceptance rate was 84%, and the top 3 accepted intervention categories were general laboratory result monitoring (96%), fluids and electrolytes (96%), and other (100%). The top 3 denied intervention categories were dose adjustment (60%), diagnostics (50%), and adding medication (22%). Conclusions : The interventions performed by the pharmacists demonstrate the unique perspective, knowledge, and importance of a pharmacist on nutrition support teams.